The impact of Traditional Gender Roles on women’s opportunities in Uzbekistan - Zumradkhon Sodikova (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
This study explores how traditional gender roles affect women’s opportunities in Uzbekistan, focusing on education, employment, and social participation. In Uzbek society, women are commonly expected to prioritize family responsibilities, while men are associated with financial provision and leadership. These expectations influence women’s life choices and limit their access to higher education, participation in the labour market, and representation in leadership roles. The analysis shows that early marriage, unpaid domestic work, and cultural norms significantly reduce women’s ability to pursue academic and professional development. In addition, despite existing legal frameworks supporting gender equality, social attitudes continue to restrict women’s advancement in decision-making positions. Overall, the findings suggest that traditional gender norms remain a key factor shaping gender inequality in Uzbekistan